2019
DOI: 10.1016/j.ebiom.2019.02.034
|View full text |Cite|
|
Sign up to set email alerts
|

MiR-873/PD-L1 axis regulates the stemness of breast cancer cells

Abstract: Background Breast cancer stem cells have self-renewal capability and are resistant to conventional chemotherapy. PD-L1 could promote the expression of stemness markers (OCT4 and Nanog) in breast cancer stem cells. However, the mechanisms by which PD-L1 regulates the stemness of breast cancer cells and PD-L1 is regulated in breast cancer cells are still unclear. Methods Lentivirus infection was used to construct stable cell lines. The correlation between PD-L1 and stemne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
94
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(101 citation statements)
references
References 47 publications
7
94
0
Order By: Relevance
“…miR-873 attenuated both the stemness and chemoresistance of BC cells via direct targeting of PD-L1, thus inactivating downstream PI3K/Akt and ERK1/2 signaling. It is notable that compared with the results of Akt/ERK1/2 inhibitors, the results of miR-873/PD-L1 in decreasing the cancer stemness are much more effective, indicating that there must be other pathways involved in the miR-873/PD-L1 axis for CSC generation [71].…”
Section: Mir-873mentioning
confidence: 97%
“…miR-873 attenuated both the stemness and chemoresistance of BC cells via direct targeting of PD-L1, thus inactivating downstream PI3K/Akt and ERK1/2 signaling. It is notable that compared with the results of Akt/ERK1/2 inhibitors, the results of miR-873/PD-L1 in decreasing the cancer stemness are much more effective, indicating that there must be other pathways involved in the miR-873/PD-L1 axis for CSC generation [71].…”
Section: Mir-873mentioning
confidence: 97%
“…Increased immune checkpoint ligands especially PD-L1 is closely related with cancerassociated miRNA expression pattern. To be more specific, previous studies have indicated that the loss of miR-3609, miR-195-5p, miR-148a-3p, miR-873, miRNA-497-5p, miR-191-5p, miR-34a, and miR-138 closely correlated with the increased PD-L1 expression on numerous cancer cells [86][87][88][89][90][91][92][93][94]. In addition, Dong et al found that decreased miR-140, miR-142, miR-340, and miR-383 enormously elevated PD-L1 expression on cervical cancer cells [95].…”
Section: Immune Checkpoint Ligand-associated Mirnasmentioning
confidence: 99%
“…PD-L1 in CSCs also confers immune evasion, thereby sustaining the tumorigenesis of CSCs [141]. Recently, miR-873-5p was shown to target PD-L1, thus attenuating breast cancer stemness [142] (Table 4).…”
Section: Mirnas Regulating Nf-κb Signaling and Pd-l1mentioning
confidence: 99%
“…Over-expression of miR-145-5p sensitizes cells to cisplatin and 5-fluorouracil in gastric cancer. This miRNA also enhances the efficacy of radiation and oxaliplatin [144,145] miR-186-5p YY1 Glioblastoma Ectopic expression of miR-186-5p improves the cisplatin cytotoxicity [149] miR-195-5p NOTCH2, RBPJ Colorectal cancer Over-expression of miR-195-5p subdues resistance to 5-fluorouracil [126] miR-196-5p SOCS1, SOCS3 Colorectal cancer Knockdown of miR-196-5p sensitizes cancer cells to 5-fluorouracil by augmenting apoptosis [129] miR-324-5p SMO, GLI1 Multiple myeloma Over-expression of miR-324-5p heightens the efficacy of bortezomib in multiple myeloma cells [135] miR-381-3p NEFL Glioblastoma Silencing of miR-381-3p increases the sensitivity of cells to temozolomide [150] miR-423-5p ING4 Glioblastoma Over-expression of miR-423-5p significantly attenuates the chemosensitivity of glioma cells to temozolomide [137] miR-450b-5p SOX2 Colorectal cancer Ectopic expression of miR-450b-5p sensitizes cells to 5-fluorouracil [143] miR-589-5p SOCS2, SOCS5, PTPN1, PTPN11 Hepatocellular carcinoma Ectopic expression of miR-589-5p promotes the emergence of acquired resistance to doxorubicin [131] miR-873-5p PD-L1 Breast cancer Over-expression of miR-873-5p attenuates therapeutic resistance to doxorubicin [142] miR-1246 CCNG2 Oral cancer Knockdown of miR-1246 sensitizes cancer cells to cisplatin [117]…”
Section: Direct Regulation Of Stemness Factorsmentioning
confidence: 99%